Fármacos quirais em diferentes matrizes ambientais: ocorrência, remoção e toxicidade - Ribeiro, Ana R. (2016)
In recent decades, the occurrence of pharmaceuticals in the environment has been widely reported due to their high frequency and recalcitrance in many cases. Concerning the chiral pharmaceuticals (CPs) in environmental matrices, the stereochemistry is often neglected and enantiomers are determined together as unique molecules. However, it is well known that CPs might have enantioselective toxicity, rendering important to assess the occurrence and degradation processes of single enantiomers in the environment, namely during biological treatment in wastewater treatment plants (WWTPs). The development of analytical methods to qualitatively and quantitatively evaluate the enantiomers of CPs is crucial for determining enantiomeric fraction (EF). The EF is the most important parameter in studies involving enantiomers and enantioselective processes and fundamental in biodegradation studies and wastewater monitoring. This review summarizes the analytical methods used to determine EF of CPs in environmental matrices and/or during biodegradation processes. The occurrence of CPs in the environment and their biodegradation are reviewed and future trends in the area outlined.